Effect of Parental Presence during Induction on Perioperative Anxiety. - Aslam, Muhammad; Ikram, Aiman; Yaqub, Qammar; Ali, Liaquat (Journal of Neonatal Surgery, 2025)
Background: Children usually develop significant anxiety before and during the induction of anesthesia because of their separation with parents, unfamiliar environment, and fear of medical processes. High levels of perioperative anxiety can result in ineffective cooperation in the process of anesthesia induction and adverse outcome of behavior after the surgery. The presence of parents at the time of administering anesthesia has been suggested as an adjuvant measure to minimize anxiety in children. Objective: To evaluate the effect of parental presence during anesthesia induction on perioperative anxiety among pediatric patients undergoing elective surgical procedures. Methodology: This is an observational comparative study carried out at Mohi ud Din Teaching Hospital Mirpur, AJK in six months between January 2025 and June 2025. Eighty-two pediatric patients who were electively admitted to undergo general anesthesia surgery were included. The children were split into two categories Group A, the use of parents during induction of anesthesia, and Group B, induction was conducted without the parents. In the preoperative area and the induction period, a scoring system on observational anxiety was used to measure anxiety levels. Inducing behavioral reactions, mask acceptance, emergence agitation and parental satisfaction were also noted. The statistical analysis of data was conducted with the help of proper statistical procedures, and a p-value was used as statistically significant at least 0.05. Results: Children in the parental presence group demonstrated significantly lower anxiety scores during anesthesia induction compared with those in the non-parental presence group. Improved cooperation during mask placement and better behavioral responses were observed among children accompanied by their parents. Furthermore, postoperative agitation was less frequent in the parental presence group, and parental satisfaction scores were significantly higher. Conclusion: Parental presence during anesthesia induction appears to be an effective non-pharmacological strategy to reduce perioperative anxiety in pediatric patients. Incorporating parental support during induction may improve the child’s behavioral response, enhance cooperation during anesthesia administration, and increase parental satisfaction..